MEMAHAMI PENGALAMAN BODY SHAMING PADA REMAJA PEREMPUAN - Tri Fajariani Fauzia; Lintang Ratri Rahmiaji (Interaksi Online, 2019)
This research was motivated by the number of cases or the phenomenon of body shaming in society. There were 966 cases of physical insult or body shaming which is handled by the police from across Indonesia throughout 2018. A total of 347 cases were completed either through law enforcement or mediation approach between victims and perpetrators. The purpose of this research is to know and understand body shaming experienced by adolescent girls. The theory used in this research is the Theory of Socialized Anxiety and Theory of Social Phenomenology. Interpretive paradigm and data analysis technique refers to the method of Clark Moustakas phenomenology. Subjects were young women who have or are experiencing body shaming. The results of this study indicate that the body shaming behavior common to all informants since middle school age and tend to be done by a school friend. The intensity of body shaming tends to rise with age and the emerging awareness of the body and appearance. The shape of body shaming is dominated by color, shape and size of the body in the form of verbal communication and even some up in the form of physical violence. Kind of Body shaming Experienced, such informants got body shaming speech in a crowded place and gets a body shaming accompanied by physical violence. Even body shaming of a male friend or lover puts more stress on the informant, with comment form unattractive body or face. Body shaming pressure and bring shame that lowers body confidence. Informants be easily sensitive to a variety of things, such as in choosing clothes, refused an invitation to leave the house, until further closing and self-limiting. Informants in this study perform verification effort to avoid the body shaming back with body treatments, a program of diet, exercise, and learn makeup. Resistance of body shaming led to the concept of body positivity, but they still take measures changes in the body'seperti dress, Forming a good body, and sensitive on matters relating to the body. Experiencing body shaming and doing body-positivity may not be completed even though they can take the fight. When the informant has been doing body positivity did not rule out the possibility they feel insecurity on his back and make changes in order to prevent the occurrence of body shaming.